Can adult education change extremist attitudes?. (1st November 2005) - Preston, John; Feinstein, Leon; Anderson, T. Marion
Abstract : Although adult education leads to a moderation of racist or authoritarian attitudes amongst the general population, little is known concerning the impact of adult education on individuals with extremist racist–authoritarian views. In this paper we group individuals from the NCDS (National Child Development Study) into various racist–authoritarian categories at ages 33 and 42 using cluster analysis. Following this identification we test various hypothesis concerning the relationship between adult education and attitude change. In particular, questioning whether adult education can transform attitudes amongst those with racist–authoritarian attitudes and/or whether adult education can sustain non-extremist views. Although there is evidence of a conditional association between adult education and sustaining non-extremist views we are sceptical concerning the ability of adult education to change extremist positions. We conclude that further work on the mechanisms linking education and extremist attitudes is required if we are to identify causal processes.